(untitled) (Research, Society and Development, 2023)
Introduction: This research proposes to analyze notifications of prescriptions for medicines subject to special control, from lists A, according to Ordinance SVS/MS nº 344 of May 12, 1998 in dispensing pharmacies, delivered to the city’s Health Surveillance (VISA). from Cascavel – Paraná. Objectives: Verify whether the standards established by the ordinance are being complied with by pharmaceutical establishments and prescribing professionals. Methods: Descriptive statistical research with a quantitative approach, based on data collection from 762 notifications of special control recipes, from the month of December 2022. Results and discussion: Of the recipes analyzed, 99 (12.84%) belonged to class A1, 667 (86.51%) to class A3, and 9 (1.16%) were illegible and were disregarded. The most prescribed medication was Methylphenidate, followed by Lisdexamfetamine. The lack of complete data on recipes was evident, with only 34 of the 762 recipes analyzed being complete. Psychiatrists were those who prescribed the most, followed by neuropediatricians and neurologists. The identification of prescriptions also presented flaws, with the patient’s address being the most problematic field. The illegibility of information related to quantity (mg) and dosage was also a concern, as this could lead to errors in pharmacological treatment. Conclusion: Pharmaceutical establishments and prescribers are partially complying with the regulations, except for the address and dispensing date fields. Identification of buyer and supplier are also elements that must be better observed and recorded, in order to ensure regulation and safety of the prescription.